Pengaruh Asset Tak Berwujud, Kebijakan Keuangan Dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan LQ45 - Dewi Perabawati; Eki Veronika; Jessica Novia; Reny Eryda; Farah Margaretha (RELASI : JURNAL EKONOMI, 2022)
The purpose of this study was to determine the effect of intangible assets, financial policies and financial performance on firm’s value. The population in this study are companies that are included in LQ45 on the Indonesia Stock Exchange (IDX). This study uses a purposive sampling method and gets a sample of 24 companies with an observation period from 2016-2019. The results showed that intangible assets had a significant positive effect on firm value. Financial policy calculated by dividends has no significant effect, while the measurement using leverage has a significant positive effect on firm value. Financial performance calculated by asset turnover and return on assets has a significant positive effect, while the calculation with the current ratio has no significant effect on firm’s value. The results of this study can be used by the company to determine the direction of policy and financial management to increase the firm’s value. Keywords: Asset turnover, Current ratio, Financial Performance, Financial Policies, Firm value, Intangible asset, leverage, return on asset